PENGARUH KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG DAN NILAI PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI) - Nuraina Elva (Jurnal Bisnis dan Ekonomi, 2012)
This research aimed to: 1) test empirically influence of institution ownership to firm value, 2). test empirically influence of firmsize to firm value, 3). test empirically influence of institution ownership to leverage, 4). test empirically influence of firm size toleverage. Population at this research is public listed company at Indonesia Stock Exchange with manufacturing company assample. Purposive sampling method use to take samples. Analysis technique that used in this research included descriptivestatistic, normality test, classic assumption and hypothesis test with linier regression.The results show that: 1) institutionownership had no significance influence on firm value, 2) firm size had significance influence on firm value, 3) institutionownership had no significance influence on leverage, 4). firm size had significance influence on leverage.Key words: institution ownership, firm size, firm value, leverage